Post-Marketing Surveillance Study to Substantiate the Efficacy and Safety for the Combination of Paracetamol, Phenylephrine, Chlorpheniramine Maleate, Sodium Citrate and Menthol in Indian Patients of Common Cold - Kiran, Dr. Mayuresh; Pawaskar, Mr. Lalit; Sheikh, Ms. Shaheen; Waghambare, Ms. Pramita (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Common cold is frequently encountered by people and it also largely affects productivity of the daily routine life. Combination of Paracetamol, Phenylephrine and Chlorpheniramine maleate which acts as an antipyretic, nasal decongestant and anti-histaminic respectively, can be used for the symptomatic treatment of common cold. To the above-mentioned combination, Sodium Citrate was added as an expectorant and Menthol for cooling effect and this post marketing surveillance study was conducted to test the efficacy and safety for the symptomatic treatment of common cold. Methodology: Out of 200 enrolled, 174 patients completed the study. Safety assessment was made by analysing the adverse events reported by the patient or their guardian. Efficacy was evaluated by total symptom score [TSS] (eleven-point scale ranging from 0 to 10 where 0 is no symptom to 10 is the maximum symptoms) which was extrapolated to four-point Likert-type symptom severity scales. Results: TSS was reduced from 5.57 at baseline visit to 3.40 at day 3 to 1.69 at day 5. At day 3 and day 5 there was TSS reduction of 38.865 % and 69.690 % respectively as compared to baseline. 18 episodes of adverse drug reactions were reported and all of them were of expected and non-serious nature. Conclusion: Fixed-dose combination of Paracetamol 125mg, Phenylephrine 5mg, Chlorpheniramine Maleate 1mg, Sodium Citrate 60mg and mentholated flavoured syrupy base q.s. per 5ml was found to be safe and efficacious for the treatment of common cold in children of age between 2 to 12 years.